Reversible DNA–Protein Cross‐Linking at Epigenetic DNA Marks. Issue 45 (6th October 2017) - Ji, Shaofei; Shao, Hongzhao; Han, Qiyuan; Seiler, Christopher L.; Tretyakova, Natalia Y.
Abstract: 5‐Formylcytosine (5fC) is an endogenous DNA modification frequently found within regulatory elements of mammalian genes. Although 5fC is an oxidation product of 5‐methylcytosine (5mC), the two epigenetic marks show distinct genome‐wide distributions and protein affinities, suggesting that they perform different functions in epigenetic signaling. A unique feature of 5fC is the presence of a potentially reactive aldehyde group in its structure. Herein, we show that 5fC bases in DNA readily form Schiff‐base conjugates with Lys side chains of nuclear proteins in vitro and in vivo. These covalent protein–DNA complexes are reversible ( t 1/2 =1.8 h), suggesting that they contribute to transcriptional regulation and chromatin remodeling. On the other hand, 5fC‐mediated DNA–protein cross‐links, if present at replication forks or actively transcribed regions, may interfere with DNA replication and transcription. Abstract : The DNA epigenetic mark 5‐formylcytosine (5fC) was found to form reversible conjugates with histone proteins in cells. The resulting DNA–protein cross‐links involve a transient Schiff‐base formation between Lys chains of proteins and the aldehyde group of 5fC. These reversible DNA–protein conjugates are likely to modify the chromatin structure and contribute to the epigenetic control of gene expression.